Implementasi pembelajaran daring: persepsi mahasiswa (studi kasus pada Program Studi Sarjana Terapan Akuntansi Perpajakan) - Winarningsiha, Srihadi; Cempaka, Adisti Gilang (Academy of Education Journal, 2024)
This research discusses student perceptions of online learning. The aim of this research is to find out students' perceptions based on their experience in taking online courses. The method used in the research is quantitative descriptive, using survey techniques in data collection. Data was obtained through a questionnaire from 272 students in Tax Accounting Applied Undergraduate Study Program at the Universitas Padjadjaran. The results of this research showed that in the online learning process students can be more independent in terms of time and location, and experience interactivity and flexibility. It was also found that limited accessibility is a challenge, faced by many students, this condition has an impact on students' social and psychological lives.